Prevalence and factors associated with suicidal ideation and attempts among war-affected internally displaced people in northwest Ethiopia, 2022 - Gebresilassie Tadesse; Fanuel Gashaw; Tadele Amare Zeleke; Setegn Fentahun; Sewbesew Yitayih (BJPsych Open, 2024)
Background People who are forced to leave home often experience emotional suffering and may be disproportionately subjected to risk factors for suicide. Although it is a grave concern for the global public health community, it has not been understood in Ethiopia.